Phototherapy - Norami de Moura Barros; Lissiê Lunardi Sbroglio; Maria de Oliveira Buffara; Jessica Lana Conceição e Silva Baka; Allen de Souza Pessoa; Luna Azulay-Abulafia (Sociedade Brasileira de Dermatologia, 2021)
Abstract Of all the therapeutic options available in Dermatology, few of them have the history, effectiveness, and safety of phototherapy. Heliotherapy, NB-UVB, PUVA, and UVA1 are currently the most common types of phototherapy used. Although psoriasis is the most frequent indication, it is used for atopic dermatitis, vitiligo, cutaneous T-cell lymphoma, and cutaneous sclerosis, among others. Before indicating phototherapy, a complete patient assessment should be performed. Possible contraindications should be actively searched for and it is essential to assess whether the patient can come to the treatment center at least twice a week. One of the main method limitations is the difficulty that patients have to attend the sessions. This therapy usually occurs in association with other treatments: topical or systemic medications. Maintaining the regular monitoring of the patient is essential to identify and treat possible adverse effects. Phototherapy is recognized for its benefits and should be considered whenever possible.